2022
DOI: 10.3390/ijerph19042124
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Responses to Multiple Bouts of Firefighting Activity: Female vs. Male Differences in a High Demand, High Performance Occupation

Abstract: While the fire service has long been a male-dominated occupation, women’s participation in this strenuous, high risk, high performance activity has increased in recent years. Firefighting induces significant cardiovascular strain, including hemostatic disruption; however, the effect of sex on hemostatic responses has not been investigated despite evidence that there are sex-related differences in hemostatic variables at rest and following exercise. Thus, we investigated hemostatic responses in age- and BMI-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…In contrast to Sackett et al [172], aPTT was decreased on average by more than three seconds (9.0% and 7.7% for females and males), indicating a procoagulatory state for both males and females following firefighting activities [169]. Although there is limited research on women, recent findings indicate no sex-dependent differences in coagulatory response to high-demand activities [169]. However, a recent cross-over study demonstrated distinct sex-specific responses in a 3-month endurance and resistance training plan regarding cardiovascular risk factors [173].…”
Section: Coagulationcontrasting
confidence: 75%
See 3 more Smart Citations
“…In contrast to Sackett et al [172], aPTT was decreased on average by more than three seconds (9.0% and 7.7% for females and males), indicating a procoagulatory state for both males and females following firefighting activities [169]. Although there is limited research on women, recent findings indicate no sex-dependent differences in coagulatory response to high-demand activities [169]. However, a recent cross-over study demonstrated distinct sex-specific responses in a 3-month endurance and resistance training plan regarding cardiovascular risk factors [173].…”
Section: Coagulationcontrasting
confidence: 75%
“…Interestingly, although fibrinogen decreased significantly in the short-term (four weeks) and increased significantly between four and eight weeks, at the eight-week time point there was no significant difference compared to baseline values [172]. In contrast to Sackett et al [172], aPTT was decreased on average by more than three seconds (9.0% and 7.7% for females and males), indicating a procoagulatory state for both males and females following firefighting activities [169]. Although there is limited research on women, recent findings indicate no sex-dependent differences in coagulatory response to high-demand activities [169].…”
Section: Coagulationmentioning
confidence: 65%
See 2 more Smart Citations